Reducing Broad-Spectrum Antimicrobial Use in Extracorporeal Membrane Oxygenation: Reduce AMMO Study. (12th February 2021) - Shah, Aditya; Sampathkumar, Priya; Stevens, Ryan W; Bohman, John K; Lahr, Brian D; Dhungana, Prabij; Vashistha, Kirtivardhan; O'Horo, John C
Abstract: Background: The use of extracorporeal membrane oxygenation (ECMO) in critically ill adults is increasing. There are currently no guidelines for antimicrobial prophylaxis. We analyzed 7 years of prophylactic antimicrobial use across 3 time series for patients on ECMO at our institution in the development, improvement, and streamlining of our ECMO antimicrobial prophylaxis protocol. Methods: In this quasi-experimental interrupted time series analysis, we evaluated the impact of an initial ECMO antimicrobial prophylaxis protocol, implemented in 2014, on antimicrobial use and National Healthcare Safety Network–reportable infection rates. Then, following a revision and streamlining of the protocol in November 2018, we reevaluated the same metrics. Results: Our study population included 338 intensive care unit patients who received ECMO between July 2011 and November 2019. After implementation of the first version of the protocol, we did not observe significant changes in antimicrobial use or infection rates in these patients; however, following revision and streamlining of the protocol, we demonstrated a significant reduction in broad-spectrum antimicrobial use for prophylaxis in patients on ECMO without any evidence of a compensatory increase in infection rates. Conclusions: Our final protocol significantly reduces broad-spectrum antimicrobial use for prophylaxis in patients on ECMO. We propose a standard antimicrobial prophylaxis regimen for patients on ECMO based on current evidence and our experience. Summary: There are no guidelines for antimicrobial prophylaxis in patients on extracorporeal membrane oxygenation (ECMO). A rational approach employing concepts of antimicrobial stewardship can drive logical antimicrobial selection for prophylaxis in patients on ECMO without adversely impacting outcomes.